Development of the Environment Readiness Index (ENRI) for Supporting Infrastructure Assessment in CNSD Facilities - Ahmad Kosasih; Dian Anggraini Purwaningtyas; Riyanto Saputro (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
The reliability of Communication, Navigation, Surveillance and Data Processing (CNSD) facilities is highly dependent on the readiness of their supporting infrastructure, including power systems, thermal and humidity control, grounding and lightning protection, physical environment, and monitoring systems. However, no integrated assessment model is currently available to comprehensively evaluate these critical supporting components. This study develops the Environment Readiness Index (EnRI) as an integrated assessment framework for measuring the readiness of supporting infrastructure in CNSD facilities. A quantitative research approach was employed through field observations, interviews, and infrastructure assessments involving 172 CNSD facilities. The proposed EnRI framework evaluates infrastructure readiness across five key domains: Thermal and Humidity Control, Power Quality and Continuity, Grounding and Lightning Protection, Physical Environment, and Monitoring and Control System (RCMS), with reference to the reliability principles of Tier III and ANSI/TIA-942. The assessment results demonstrate that EnRI effectively identifies infrastructure readiness levels, determines gaps against established standards, and supports the prioritization of infrastructure improvement programs. The proposed framework provides a systematic decision-support tool for infrastructure evaluation, investment planning, and continuous improvement of CNSD facility reliability. Unlike existing assessment approaches that evaluate supporting infrastructure separately, EnRI integrates five critical infrastructure domains into a unified readiness assessment framework specifically designed for CNSD facilities.